2022
DOI: 10.1038/s41598-022-24275-6
|View full text |Cite
|
Sign up to set email alerts
|

Melt electrowriting of PLA, PCL, and composite PLA/PCL scaffolds for tissue engineering application

Abstract: Fabrication of well-ordered and bio-mimetic scaffolds is one of the most important research lines in tissue engineering. Different techniques have been utilized to achieve this goal, however, each method has its own disadvantages. Recently, melt electrowriting (MEW) as a technique for fabrication of well-organized scaffolds has attracted the researchers’ attention due to simultaneous use of principles of additive manufacturing and electrohydrodynamic phenomena. In previous research studies, polycaprolactone (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 67 publications
1
22
0
Order By: Relevance
“…Similarly, studies concerning melt electrowriting of PLA reported difficulties in the accurate positioning of the PLA fibers due to high PLA viscosity [ 44 ]. Some authors reported the addition of sodium stearate to reduce the melt viscosity of PLA during electrospinning, which also resulted in a reduction of fiber diameter [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, studies concerning melt electrowriting of PLA reported difficulties in the accurate positioning of the PLA fibers due to high PLA viscosity [ 44 ]. Some authors reported the addition of sodium stearate to reduce the melt viscosity of PLA during electrospinning, which also resulted in a reduction of fiber diameter [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…PCL has a slow degradation property [ 47 ]; the most significant advantage of PCL prepared in our study is that they can release drugs in vitro for a long time (at least 35 days), which allows the maintenance of local drug therapy for a significantly longer period after cancer surgery. In addition, PCL is easy to be processed due to its good mechanical properties and is usually fabricated as an extremely thin and softer sheet [ 48 ]. This makes it compatible with the hard and soft tissues of the body, markedly mitigating the risk of poor wound healing and bleeding post-implantation.…”
Section: Discussionmentioning
confidence: 99%
“…MTT, as a quantitative cell viability test, was used to study the cell compatibility of the scaffolds. 43 The samples were each placed in sterile 24-well plates and submerged in 70% ethanol solution for 3 h. Then each side of the samples was exposed to UV light for 1 hour. Afterwards, the samples were washed 3 times with sterile PBS, for 20 minutes each time.…”
Section: Cell Viabilitymentioning
confidence: 99%